Wound healing potential of Vakeri fortified Kampillakadi Taila - Pranjali P. Dhawal; Milind Gharpure; Minal S. Joshi; Rummana R. Khan; Sidhivinayak S. Barve (Journal of Ayurveda and Integrative Medicine, 2023)
Background: Traditional medicine in form of decoctions has been known for ages to possess wound healing abilities. One such traditional formulation mentioned in Indian literature Charak Samhita Chikitsa Sthanam is Kampillakadi Taila and tremendous information is available on its implication in the treatment of skin cuts and wounds, diseases, or bacterial infections. This research paper focuses on studying the wound healing property of one such herbal proprietary formulation known as a wound healing oil, derived from Kampillakadi Taila fortified with root extract of Wagatea spicata (VIKHPF). Objective: The current research is aimed at studying chemical profiling, antioxidant activity, antimicrobial efficacy, in-vitro cell proliferating, and in-vitro wound healing activity of this VKHPF. Materials and methods: The chemical characterization of VKHPF was done by gas chromatography- fatty acid methyl esters GC-FAME analysis for lipid analysis and gas chromatography high-resolution mass spectrometry (GC-HRMS)for revealing its chemical constituents. Proliferation and migration are two underlying mechanisms involved in the healing of wounds. Hence, in-vitro studies such as cell proliferation assay and in-vitro scratch test on NIH/3T3 mice fibroblast cell line were conducted were used to determine in-vitro wound healing capacity of VKHPF. The oil was also tested for antioxidant effect (DPPH assay) and anti-microbial potential (Time kill test). Results: The GC-HRMS and GC-FAME analyses revealed rich medicinally important fatty acids and vitamins were present in VKHPF, such as oleic acid, hexadecanoic acid, squalene, α, γ-tocopherol, γ-sitosterol, and benzoic acid. VKHPF at 0.5 mg/ml in media without serum showed 164.00 ± 0.011% cell viability with 64.00% cell proliferation in contrast to media containing serum (100% cell viability). At the same concentration, the wound closure was 98% for VKHPF. The oil sample possessed antioxidant activity with an IC50 value of 3.5 mg/ml and antimicrobial activity against Staphylococcus aureus and Pseudomonas aeruginosa when tested using Time Kill Activity. Conclusion: This study is the first to report the use of Vakeri fortified Kampillakadi Taila herbal proprietary formulation (VKHPF) in in-vitro wound healing and the present data suggest that it can form a part of modern medicine.